Multicast traffic grooming in future internet over optical networks - Wang, Yang. (2010)
IP/MPLS over WDM network is a very promising candidate powerful tool for the future generation optical internet network. To manipulate such a network effectively and efficiently, traffic grooming plays a main role of inter connection between WDM network that supplies bandwidth at the wavelength granularity. Among the methods of traffic grooming, dynamic traffic grooming is more advantaged and practical for simulation. In this report, the objective is to implement, compare and improve three methods of traffic grooming, that is single-hop grooming, multi-hop grooming (two hops) and path grooming. Firstly, literature review on history of the evolution of telecom network; advanced technology in optical network and different traffic grooming methods in WDM mesh networks are presented. Secondly, methods of single-hop grooming, multi-hop grooming and path grooming are shown as well as simulation framework. An improved method of single hop grooming is implemented to improve the blocking probability performance. Finally, three methods of traffic grooming are compared and discussed based on blocking probability under different traffic loads and destination numbers, and the path grooming turns out technique to be the best among the three methods.